Liquid platelet-rich fibrin injections as a treatment adjunct for painful temporomandibular joints: preliminary results. Issue 5 (2nd September 2020) - Albilia, Jonathan; Herrera-Vizcaíno, Carlos; Weisleder, Hillary; Choukroun, Joseph; Ghanaati, Shahram
ABSTRACT: Objective: To evaluate the clinical benefits of liquid platelet-rich fibrin (PRF) in patients with temporomandibular joint (TMJ) pain and dysfunction. Methods: Forty-eight TMJs in 37 patients with painful internal derangement (ID) (Wilkes' I–V) were included. Patients were injected with 1.5–2cc of PRF within the superior joint space at 2-week intervals. Pain and subjective dysfunction were recorded using a visual analog scale. Statistical analyses were done using the ANOVA test. Results: Thirty-three of 48 TMJs (69%) showed significant reduction in pain at 8 weeks, and at 3, 6, and 12 months (Responders). Fifteen of 48 TMJs (31%) did not improve (Non-responders). The best Responders to liquid PRF injections were ID stages Wilkes' IV (78.5%) and V (100%), compared to Wilkes' I (0%), II (47%), and III (33%). A non-significant, but notable decrease in dysfunction was found. Conclusion: Preliminary findings support that liquid PRF exhibits long-term analgesic effects in most patients with painful TMJ ID.